Difficult-to-fade color master batch for lawn and preparation method thereof

By using porous materials with different pore sizes and electrospinning methods, the fading problem of artificial turf pigments in sun and rain is solved, the light resistance and anti-aging properties of the pigments are improved, and the pigments are achieved higher pigment stability and matrix compatibility.

CN119192711AActive Publication Date: 2024-12-27HUAIAN TENGDA COLOR MASTERBATCH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411575188.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2024-12-27
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Artificial turf is prone to fading pigments due to sun and rain when used outdoors, and its anti-aging performance is insufficient, so the existing technology is difficult to effectively solve this problem.

Method used

The pigment is adsorbed with porous materials of different pore sizes and made fibers by electrospinning. The nanocoating is formed by electrostatic interaction between chitosan and concave rock stone nanorods, which is wrapped around the fibers to improve the stability of the pigment and Light resistance, while enhancing compatibility and dispersion with the matrix resin.

Benefits of technology

It significantly improves the adsorption rate and load capacity of the pigment, enhances the light resistance and aging stability of the pigment, extends the service life of the pigment, and improves compatibility and dispersion with the matrix resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192711A_ABST
    Figure CN119192711A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: stirring and mixing low-density polyethylene, polyethylene wax and magnesium stearate at a high speed, and heating to a constant temperature until the polyethylene wax is completely molten; adding high-stability pigment particles, and stirring until the surface of the low-density polyethylene is coated with a large number of high-stability pigment particles to obtain a mixture; and heating a twin-screw extruder to 130 DEG C, adding the mixture, extruding and granulating to obtain the color master batch which is not easy to fade and used for the lawn. According to the preparation method, pigment-loaded modified porous materials with different apertures are prepared into fibers by adopting an electrostatic spinning method, then an interphase is formed among electrostatic spinning membrane fibers by utilizing electrostatic interaction between positively charged chitosan and negatively charged attapulgite nanorods, each fiber is coated with the interphase, and a nano coating is formed; and a strong and compact interface is formed, so that the stability of the pigment is protected, the light resistance and the aging resistance stability are improved, and meanwhile, the compatibility and the dispersity between the pigment and matrix resin can also be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of masterbatch materials, and in particular to a non-fading masterbatch for lawns and a preparation method thereof. Background Art

[0002] Human beings have a long history of using pigments to color plastics, but it has only been about 40 to 50 years since pigments were made into masterbatches for coloring. The first industries to use masterbatches were the cable and synthetic fiber industries. Due to the continuous improvement of masterbatch production technology and the advanced application of masterbatches, they have been widely used in packaging materials, automotive plastics, household appliances and agricultural plastics, making the masterbatch industry have made great progress. The research and development of masterbatches in my country began in the mid-1970s. At that time, due to the start of construction of Yanshan and Liaohua polypropylene production facilities in my country, my country's polypropylene fiber has developed rapidly. Since polypropylene fiber does not have a dye that can be dyed, the use of masterbatches for stock coloring is the only way to solve its coloring. Since then, various parts of my country have begun to study masterbatches, taking the first step in the development of masterbatches in my country. At present, masterbatch coloring is widely used in the fields of plastic products such as films, plastic products, and chemical fibers, including artificial turf materials. Since masterbatches for artificial turf are used outdoors, they must be exposed to the sun and rain, and their fading is a problem that must be solved. How to improve its fading resistance and anti-aging performance is a problem that needs to be solved at present. Summary of the invention

[0003] Technical problem to be solved: The purpose of the present invention is to provide a non-fading masterbatch for lawns and a preparation method thereof, wherein porous materials with different pore sizes are used to adsorb pigments, and the pores with different pore sizes can promote the internal diffusion of pigment molecules, reduce external mass transfer resistance, and allow pigment molecules to reach the adsorption site faster, thereby accelerating the adsorption rate and loading amount; and an electrostatic spinning method is used to make fibers with modified porous materials with different pore sizes loaded with pigments, and then the electrostatic interaction between positively charged chitosan and negatively charged attapulgite nanorods is utilized to form an interphase between the electrospinning membrane fibers, which is wrapped around each fiber to form a nano coating, forming a strong and dense interface, thereby protecting the stability of the pigment, improving the light resistance and aging resistance, and at the same time improving the compatibility and dispersibility with the matrix resin.

[0004] Technical solution: A non-fading masterbatch for lawns, comprising the following raw materials in parts by weight: 10 to 18 parts of high-stability pigment particles, 100 parts of low-density polyethylene, 12 parts of polyethylene wax, and 8 parts of magnesium stearate. Furthermore, the preparation method of the high stability pigment particles is as follows: Step 1: dissolving chitosan in 3% acetic acid solution to prepare 0.5-2 g / L chitosan acetic acid solution, adding porous materials with different pore sizes, reacting for 6 hours with magnetic stirring, centrifuging at 9000 rpm for 5 minutes to separate the solid and liquid, washing the solid and drying it at 70°C, and grinding it to obtain modified porous materials with different pore sizes; Step 2: 25-50 mg of the pigment is dissolved / dispersed in 1 L of ultrapure water to form a pigment solution / suspension, 2-4 g of the modified porous material with different pore sizes is dispersed in the pigment solution, magnetically stirred for 2-4 h, centrifuged at 9000 rpm for 5 min to separate the solid and liquid, the solid is washed and dried at 70° C., and the modified porous material with different pore sizes loaded with the pigment is obtained after grinding; Step 3: prepare a PVP / ethanol solution with a mass concentration of 10-14%, add the modified porous materials with different pore sizes loaded with pigments, stir evenly and place in an electrospinning device for electrospinning to obtain a porous fiber membrane coated with pigments; Step 4: remove the pigment-coated porous fiber membrane, put it into a vacuum drying oven at 70°C, crush it, and pass it through a 200-mesh sieve to obtain pigment-coated porous fiber membrane particles with a porosity of 60-80% and a pore size of 10-50 μm; Step 5: dissolving chitosan in 3% acetic acid solution to prepare a 0.5-2 g / L chitosan acetic acid solution; taking 50 mg of attapulgite nanorods, adding 50 mL of PBS buffer, and ultrasonically dispersing to obtain a attapulgite nanorod suspension; Step 6: immerse 50 mg of the pigment-coated porous fiber membrane particles in 100 mL of chitosan acetic acid solution for 1 to 2 h; Step 7: Add the attapulgite nanorod suspension, stir and mix evenly, and perform electrostatic assembly reaction at room temperature for 4 to 5 hours; Step 8: Take out the reactants, wash with water, and freeze-dry to obtain highly stable pigment particles. Furthermore, the preparation method of the porous materials with different pore sizes in step 1 is as follows: S1: Take 3g MgO, 18g Al 2 O 3 and 80g SiC powder were mixed evenly, 0.8wt.% sodium carboxymethyl cellulose solution was added, and the pH was adjusted to 10 to obtain a ceramic slurry with a solid content of 25-40vol.%; S2: placing the ceramic slurry in a ball mill for ball milling, the ball milling time is 10 h, and the rotation speed is 100 r / min; S3: adding the milled ceramic slurry to PS microspheres of different particle sizes, stirring evenly, injecting into the mold, and centrifuging at 4000-6000 rpm for 30-50 min on a centrifuge; S4: Immerse the bottom of the mold in a liquid cold source at -120°C to -30°C and freeze it quickly; S5: freeze-drying at a temperature of -50°C and a pressure of 0-50Pa to obtain porous ceramic preforms with different pore sizes; S6: Place the porous ceramic preforms with different pore sizes into an atmosphere box furnace, keep them in air at 385°C for 20 minutes, then heat them to 1200°C for 1 hour, introduce argon gas for liquid phase sintering after vacuuming, heat them to 1500°C for 2 hours, and heat them at a rate of 5°C / min. Furthermore, the addition amount of the PS microspheres with different particle sizes is 1-2% of the volume of the ceramic slurry, the particle sizes are 10-30 nm and 100-170 nm respectively, and the volume ratio is 1:1. Furthermore, in step 1, the volume mass ratio of the chitosan acetic acid solution and the porous materials with different pore sizes is 1L:(50-130)g. Furthermore, the particle size of the modified porous material with different pore sizes loaded with the pigment in step 2 is 2 to 20 μm. Furthermore, in step 3, the volume mass ratio of the PVP / ethanol solution to the modified porous materials with different pore sizes is 20 mL: (1-2) g. Furthermore, the electrospinning conditions in step 3 are: spinning temperature of 20-26° C., humidity of 20-30%, spinning solution flow rate of 0.5-0.8 mL / h, needle outer diameter of 0.8 mm, inner diameter of 0.5 mm, and receiving distance of 13-16 cm. The method for preparing the above-mentioned non-fading masterbatch for lawn comprises the following steps: Step 1: Mix low-density polyethylene, polyethylene wax and magnesium stearate with high-speed stirring, and heat to 80° C. and maintain the temperature until the polyethylene wax is completely melted; Step 2: Add high-stability pigment particles and stir until a large amount of high-stability pigment particles are coated on the surface of the low-density polyethylene to obtain a mixture; Step 3: After the twin-screw extruder is heated to 130°C, add the mixed material, extrude and granulate at a temperature of 120-140°C to obtain the non-fading masterbatch for lawn use. Beneficial effects: 1. The present invention uses porous materials with different pore sizes to adsorb pigments. Porous materials with different pore sizes can promote the internal diffusion of pigment molecules, reduce external mass transfer resistance, and enable pigment molecules to reach the adsorption site faster, thereby accelerating the adsorption rate and loading capacity. 2. The present invention uses chitosan to modify porous materials with different pore sizes, thereby providing more adsorption sites, which can adsorb more pigments, thereby further increasing the pigment loading capacity of the porous materials. 3. The present invention adopts an electrospinning method to make modified porous materials with different pore sizes loaded with pigments into fibers, and then utilizes the electrostatic interaction between positively charged chitosan and negatively charged attapulgite nanorods to form an interphase between the electrospinning membrane fibers, which is wrapped around each fiber to form a nano coating, forming a strong and dense interface, thereby protecting the stability of the pigment, improving the light resistance and aging resistance, and at the same time improving the compatibility and dispersibility with the matrix resin. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is a graph showing the light resistance stability test results of the pigment particles prepared in Examples 7 to 9, Comparative Example 3 and Comparative Example 5. DETAILED DESCRIPTION Example 1 The preparation methods of porous materials with different pore sizes are as follows: S1: Take 3g MgO, 18g Al 2 O 3 and 80 g SiC powder were mixed evenly, 0.8 wt.% sodium carboxymethyl cellulose solution was added, and the pH was adjusted to 10 to obtain a ceramic slurry with a solid content of 30 vol.%; S2: placing the ceramic slurry in a ball mill for ball milling, the ball milling time is 10 h, and the rotation speed is 100 r / min; S3: The ceramic slurry after ball milling was added with PS microspheres of different particle sizes, stirred evenly, injected into a mold, and centrifuged at 4000 rpm for 50 min on a centrifuge; the addition amount of PS microspheres of different particle sizes was 1% of the volume of the ceramic slurry, and the particle sizes were 10-30 nm and 100-170 nm, respectively, with a volume ratio of 1:1; S4: Immerse the bottom of the mold in a liquid cold source at -100°C for rapid freezing; S5: freeze-drying at a temperature of -50°C and a pressure of 5 Pa to obtain porous ceramic preforms with different pore sizes; S6: Place the porous ceramic preforms with different pore sizes into an atmosphere box furnace, keep them in air at 385°C for 20 minutes, then heat them to 1200°C for 1 hour, introduce argon gas for liquid phase sintering after vacuuming, heat them to 1500°C for 2 hours, and heat them at a rate of 5°C / min. After testing, it was found that the pore sizes of porous materials with different pore sizes were distributed relatively evenly, with pore sizes ranging from 2 to 5 nm, 10 to 30 nm, and 100 to 170 nm. Example 2 The preparation methods of porous materials with different pore sizes are as follows: S1: Take 3g MgO, 18g Al 2 O 3and 80 g SiC powder were mixed evenly, 0.8 wt.% sodium carboxymethyl cellulose solution was added, and the pH was adjusted to 10 to obtain a ceramic slurry with a solid content of 30 vol.%; S2: placing the ceramic slurry in a ball mill for ball milling, the ball milling time is 10 h, and the rotation speed is 100 r / min; S3: The ceramic slurry after ball milling was added with PS microspheres of different particle sizes, stirred evenly, injected into a mold, and centrifuged at 5000 rpm for 40 min on a centrifuge; the addition amount of PS microspheres of different particle sizes was 1.5% of the volume of the ceramic slurry, and the particle sizes were 10-30 nm and 100-170 nm, respectively, with a volume ratio of 1:1; S4: Immerse the bottom of the mold in a liquid cold source at -100°C for rapid freezing; S5: freeze-drying at a temperature of -50°C and a pressure of 5 Pa to obtain porous ceramic preforms with different pore sizes; S6: Place the porous ceramic preforms with different pore sizes into an atmosphere box furnace, keep them in air at 385°C for 20 minutes, then heat them to 1200°C for 1 hour, introduce argon gas for liquid phase sintering after vacuuming, heat them to 1500°C for 2 hours, and heat them at a rate of 5°C / min. After testing, it was found that the pore sizes of porous materials with different pore sizes were evenly distributed, with pore sizes of 1-3 nm, 10-30 nm and 100-170 nm. Example 3 The preparation methods of porous materials with different pore sizes are as follows: S1: Take 3g MgO, 18g Al 2 O 3 and 80 g SiC powder were mixed evenly, 0.8 wt.% sodium carboxymethyl cellulose solution was added, and the pH was adjusted to 10 to obtain a ceramic slurry with a solid content of 30 vol.%; S2: placing the ceramic slurry in a ball mill for ball milling, the ball milling time is 10 h, and the rotation speed is 100 r / min; S3: The ball-milled ceramic slurry was added with PS microspheres of different particle sizes, stirred evenly, injected into a mold, and centrifuged at 6000 rpm for 30 min on a centrifuge; the addition amount of PS microspheres of different particle sizes was 2% of the volume of the ceramic slurry, and the particle sizes were 10-30 nm and 100-170 nm, respectively, with a volume ratio of 1:1; S4: Immerse the bottom of the mold in a liquid cold source at -100°C for rapid freezing; S5: freeze-drying at a temperature of -50°C and a pressure of 5 Pa to obtain porous ceramic preforms with different pore sizes; S6: Place the porous ceramic preforms with different pore sizes into an atmosphere box furnace, keep them in air at 385°C for 20 minutes, then heat them to 1200°C for 1 hour, introduce argon gas for liquid phase sintering after vacuuming, heat them to 1500°C for 2 hours, and heat them at a rate of 5°C / min. After testing, it was found that the pore sizes of porous materials with different pore sizes were distributed relatively evenly, with pore sizes of 1-2nm, 10-30nm and 100-170nm. Comparative Example 1 The preparation method of the porous material is as follows: S1: Take 3g MgO, 18g Al 2 O 3 and 80 g SiC powder were mixed evenly, 0.8 wt.% sodium carboxymethyl cellulose solution was added, and the pH was adjusted to 10 to obtain a ceramic slurry with a solid content of 30 vol.%; S2: placing the ceramic slurry in a ball mill for ball milling, the ball milling time is 10 h, and the rotation speed is 100 r / min; S3: Add the ceramic slurry after ball milling to PS microspheres of the same particle size, stir evenly, inject into the mold, and centrifuge at 5000 rpm for 40 minutes on a centrifuge; the amount of PS microspheres added is 1.5% of the volume of the ceramic slurry, and the particle size is 100-170 nm; S4: Immerse the bottom of the mold in a liquid cold source at -100°C for rapid freezing; S5: freeze-drying at a temperature of -50°C and a pressure of 5 Pa to obtain porous ceramic preforms with different pore sizes; S6: Place the porous ceramic preforms with different pore sizes into an atmosphere box furnace, keep them in air at 385°C for 20 minutes, then heat them to 1200°C for 1 hour, introduce argon gas for liquid phase sintering after vacuuming, heat them to 1500°C for 2 hours, and heat them at a rate of 5°C / min. The test showed that the pore size distribution of the porous material was uniform, with pore sizes ranging from 1 to 3 nm and from 100 to 170 nm. Example 4 The following tests were conducted using porous materials with different pore sizes prepared in Example 1 (result naming: Example 4-1), Example 2 (result naming: Example 4-2), Example 3 (result naming: Example 4-3) and Comparative Example 1 (result naming: Comparative Example 2): Preparation of pigment-loaded modified porous materials with different pore sizes: Step 1: Dissolve chitosan in 3% acetic acid solution to prepare 1L 0.5g / L chitosan acetic acid solution, add 100g of porous materials with different pore sizes, react for 6h with magnetic stirring, centrifuge at 9000rpm for 5min to separate solid and liquid, wash the solid and dry it at 70℃, grind it to obtain modified porous materials with different pore sizes; Step 2: Disperse 400 mg of phthalocyanine green G in 10 L of ultrapure water to form a phthalocyanine green G suspension, take 20 g of modified porous materials with different pore sizes and disperse them in the pigment solution, stir magnetically for 3 hours, centrifuge at 9000 rpm for 5 minutes to separate the solid and liquid, wash the solid and dry it at 70°C, and grind it to obtain modified porous materials with different pore sizes loaded with pigments with a particle size of 2 to 20 μm. Example 5 The following tests were conducted using porous materials with different pore sizes prepared in Example 1 (result naming: Example 5-1), Example 2 (result naming: Example 5-2), Example 3 (result naming: Example 5-3) and Comparative Example 1 (result naming: Comparative Example 3): Preparation of pigment-loaded modified porous materials with different pore sizes: Step 1: dissolving chitosan in 3% acetic acid solution to prepare 1L 1.5g / L chitosan acetic acid solution, adding 100g of porous materials with different pore sizes prepared in Example 2, reacting for 6h with magnetic stirring, centrifuging at 9000rpm for 5min to separate the solid and liquid, washing the solid and drying it at 70°C, and grinding it to obtain modified porous materials with different pore sizes; Step 2: Disperse 400 mg of phthalocyanine green G in 10 L of ultrapure water to form a phthalocyanine green G suspension, take 30 g of modified porous materials with different pore sizes and disperse them in the pigment solution, stir magnetically for 3 hours, centrifuge at 9000 rpm for 5 minutes to separate the solid and liquid, wash the solid and dry it at 70°C, and grind it to obtain modified porous materials with different pore sizes loaded with pigments with a particle size of 2 to 20 μm. Example 6 The following tests were conducted using porous materials with different pore sizes prepared in Example 1 (result naming: Example 6-1), Example 2 (result naming: Example 6-2), Example 3 (result naming: Example 6-3) and Comparative Example 1 (result naming: Comparative Example 4): Preparation of pigment-loaded modified porous materials with different pore sizes: Step 1: dissolving chitosan in 3% acetic acid solution to prepare 1L 2g / L chitosan acetic acid solution, adding 100g of porous materials with different pore sizes prepared in Example 2, reacting by magnetic stirring for 6h, centrifuging at 9000rpm for 5min to separate the solid and liquid, washing the solid and drying it at 70°C, and grinding it to obtain modified porous materials with different pore sizes; Step 2: Disperse 400 mg of phthalocyanine green G in 10 L of ultrapure water to form a phthalocyanine green G suspension, take 40 g of modified porous materials with different pore sizes and disperse them in the pigment solution, stir magnetically for 3 hours, centrifuge at 9000 rpm for 5 minutes to separate the solid and liquid, wash the solid and dry it at 70°C, grind it to obtain a pigment-loaded modified porous material with different pore sizes with a particle size of 2 to 20 μm. The loading amount of the pigment-loaded modified porous materials with different pore sizes is measured, and the results are shown in Table 1 below: Table 1 From the perspective of pigment loading and economy, the modified porous materials with different pore sizes loaded with pigments obtained in Example 5-2 were selected for the next step of the experiment. Example 7 Preparation of high stability pigment particles: Step 1: prepare 200 mL of 10% PVP / ethanol solution, add 10 g of modified porous materials with different pore sizes loaded with pigments, stir evenly and place in an electrospinning device for electrospinning. The electrospinning conditions are: spinning temperature of 24 ° C, humidity of 26%, spinning solution flow rate of 0.5 mL / h, needle outer diameter of 0.8 mm, inner diameter of 0.5 mm, receiving distance of 13 cm, and obtain a porous fiber membrane coated with pigments; Step 2: The pigment-encapsulated porous fiber membrane is removed, placed in a vacuum drying oven at 70°C for drying, crushed, and passed through a 200-mesh sieve to obtain pigment-encapsulated porous fiber membrane particles having a porosity of 67.2% and a pore size of 10 to 30 μm; Step 3: dissolving chitosan in 3% acetic acid solution to prepare a 1.5 g / L chitosan acetic acid solution; taking 5 g of attapulgite nanorods, adding 5 L of PBS buffer, and ultrasonically dispersing to obtain a attapulgite nanorod suspension; Step 4: immerse 5 g of the pigment-coated porous fiber membrane particles in 10 L of chitosan acetic acid solution for 2 h; Step 5: Add the attapulgite nanorod suspension, stir and mix evenly, and perform electrostatic assembly reaction at room temperature for 4.5 hours; Step 6: Take out the reactants, wash with water, and freeze-dry to obtain highly stable pigment particles. Example 8 Preparation of high stability pigment particles: Step 1: prepare 200 mL of a 12% PVP / ethanol solution, add 15 g of modified porous materials with different pore sizes loaded with pigments, stir evenly and place in an electrospinning device for electrospinning. The electrospinning conditions are: spinning temperature of 24 ° C, humidity of 26%, spinning solution flow rate of 0.7 mL / h, needle outer diameter of 0.8 mm, inner diameter of 0.5 mm, receiving distance of 15 cm, and obtain a porous fiber membrane coated with pigments; Step 2: The pigment-encapsulated porous fiber membrane is removed, placed in a vacuum drying oven at 70°C for drying, crushed, and passed through a 200-mesh sieve to obtain pigment-encapsulated porous fiber membrane particles having a porosity of 71.3% and a pore size of 15 to 40 μm; Step 3: dissolving chitosan in 3% acetic acid solution to prepare a 1.5 g / L chitosan acetic acid solution; taking 5 g of attapulgite nanorods, adding 5 L of PBS buffer, and ultrasonically dispersing to obtain a attapulgite nanorod suspension; Step 4: immerse 5 g of the pigment-coated porous fiber membrane particles in 10 L of chitosan acetic acid solution for 2 h; Step 5: Add the attapulgite nanorod suspension, stir and mix evenly, and perform electrostatic assembly reaction at room temperature for 4.5 hours; Step 6: Take out the reactants, wash with water, and freeze-dry to obtain highly stable pigment particles. Example 9 Preparation of high stability pigment particles: Step 1: prepare 200 mL of a 14% PVP / ethanol solution, add 20 g of modified porous materials with different pore sizes loaded with pigments, stir evenly and place in an electrospinning device for electrospinning. The electrospinning conditions are: spinning temperature of 24 ° C, humidity of 26%, spinning solution flow rate of 0.8 mL / h, needle outer diameter of 0.8 mm, inner diameter of 0.5 mm, receiving distance of 16 cm, and obtain a porous fiber membrane coated with pigments; Step 2: The pigment-encapsulated porous fiber membrane is removed, placed in a vacuum drying oven at 70°C for drying, crushed, and passed through a 200-mesh sieve to obtain pigment-encapsulated porous fiber membrane particles having a porosity of 75.6% and a pore size of 20 to 50 μm; Step 3: dissolving chitosan in 3% acetic acid solution to prepare a 1.5 g / L chitosan acetic acid solution; taking 5 g of attapulgite nanorods, adding 5 L of PBS buffer, and ultrasonically dispersing to obtain a attapulgite nanorod suspension; Step 4: immerse 5 g of the pigment-coated porous fiber membrane particles in 10 L of chitosan acetic acid solution for 2 h; Step 5: Add the attapulgite nanorod suspension, stir and mix evenly, and perform electrostatic assembly reaction at room temperature for 4.5 hours; Step 6: Take out the reactants, wash with water, and freeze-dry to obtain highly stable pigment particles. Comparative Example 5 The difference between this comparative example and Example 9 is that the modified porous material with different pore sizes loaded with pigments obtained in Example 5-2 is not used for the next test, but the modified porous material with different pore sizes loaded with pigments prepared in Comparative Example 3 is used, and the other conditions remain unchanged. Light stability test: The light stability of high-stability pigment particles was tested using UV diffuse reflectance-visible spectrophotometry. The sample was irradiated with a UV lamp with a wavelength of 395nm, a power of 50W, and a light intensity of 550mW / cm 2 , illuminate for 120 hours, calculate the color difference, the smaller the color difference, the better the light resistance stability. The results are shown in Table 2 and Figure 1 shown. Table 2 By comparison, the high-stability pigment particles prepared in Example 9 were used to prepare non-fading masterbatch for lawns. Example 10 The method for preparing non-fading masterbatch for lawn comprises the following steps: Step 1: 1000 g of low-density polyethylene, 120 g of polyethylene wax and 80 g of magnesium stearate are mixed by high-speed stirring, and heated to 80° C., and the temperature is maintained until the polyethylene wax is completely melted; Step 2: Add 100 g of high-stability pigment particles and stir until a large amount of high-stability pigment particles are coated on the surface of the low-density polyethylene to obtain a mixture; Step 3: After the twin-screw extruder is heated to 130°C, add the mixed material and control the temperatures of zones 1 to 6 of the twin-screw extruder as follows: zone 1 130°C, zone 2 135°C, zone 3 140°C, zone 4 135°C, zone 5 125°C, zone 6 120°C. Extrude and granulate to obtain non-fading masterbatch for lawns. Embodiment 11 The method for preparing a non-fading masterbatch for lawns comprises the following steps: Step 1: 1000 g of low-density polyethylene, 120 g of polyethylene wax and 80 g of magnesium stearate are mixed by high-speed stirring, and heated to 80° C., and the temperature is maintained until the polyethylene wax is completely melted; Step 2: Add 150 g of high-stability pigment particles and stir until a large amount of high-stability pigment particles are coated on the surface of the low-density polyethylene to obtain a mixture; Step 3: After the twin-screw extruder is heated to 130°C, add the mixed material and control the temperatures of zones 1 to 6 of the twin-screw extruder as follows: zone 1 130°C, zone 2 135°C, zone 3 140°C, zone 4 135°C, zone 5 125°C, zone 6 120°C. Extrude and granulate to obtain non-fading masterbatch for lawns. Example 12 The method for preparing a non-fading masterbatch for lawns comprises the following steps: Step 1: 1000 g of low-density polyethylene, 120 g of polyethylene wax and 80 g of magnesium stearate are mixed by high-speed stirring, and heated to 80° C., and the temperature is maintained until the polyethylene wax is completely melted; Step 2: Add 180 g of high-stability pigment particles and stir until a large amount of high-stability pigment particles are coated on the surface of the low-density polyethylene to obtain a mixture; Step 3: After the twin-screw extruder is heated to 130°C, add the mixed material and control the temperatures of zones 1 to 6 of the twin-screw extruder as follows: zone 1 130°C, zone 2 135°C, zone 3 140°C, zone 4 135°C, zone 5 125°C, zone 6 120°C. Extrude and granulate to obtain non-fading masterbatch for lawns. Comparative Example 6 The difference between this comparative example and Example 11 is that the high-stability pigment particles prepared in Example 9 are not used for the next test, but the modified porous materials with different pore sizes loaded with pigments prepared in Comparative Example 3 are used, and the other conditions remain unchanged. Comparative Example 7 The difference between this comparative example and Example 11 is that the high-stability pigment particles prepared in Example 9 are not used for the next test, but the pigment particles prepared in Comparative Example 5 are used, and the other conditions remain unchanged. The non-fading masterbatch for lawn prepared in each embodiment was tested for various properties: Color difference and UV aging resistance test: at a wavelength of 315-400nm and a light intensity of 6000μW / cm 2 The color difference (△E) and elongation at break retention of each color masterbatch after exposure to ultraviolet light for 30 days were measured according to GB / T 1040 "Determination of tensile properties of plastics". The test results are shown in Table 3 below: Table 3 The above embodiments are intended to provide a clear and complete description of the technical solution, and are partial implementations of the present invention, rather than all implementations. However, the implementations of the present invention are not limited to the above embodiments, and any other changes, modifications, substitutions, combinations or simplifications that do not deviate from the spirit and principle of the present invention shall be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A non-fading masterbatch for lawns, characterized by: The invention comprises the following raw materials in parts by weight: 10 to 18 parts of high-stability pigment particles, 100 parts of low-density polyethylene, 12 parts of polyethylene wax and 8 parts of magnesium stearate.

2. The non-fading masterbatch for lawn use according to claim 1, characterized in that: The preparation method of the high stability pigment particles is as follows: Step 1: dissolving chitosan in 3% acetic acid solution to prepare 0.5-2 g / L chitosan acetic acid solution, adding porous materials with different pore sizes, reacting for 6 hours with magnetic stirring, centrifuging at 9000 rpm for 5 minutes to separate the solid and liquid, washing the solid and drying it at 70°C, and grinding it to obtain modified porous materials with different pore sizes; Step 2: 25-50 mg of the pigment is dissolved / dispersed in 1 L of ultrapure water to form a pigment solution / suspension, 2-4 g of the modified porous material with different pore sizes is dispersed in the pigment solution, magnetically stirred for 2-4 h, centrifuged at 9000 rpm for 5 min to separate the solid and liquid, the solid is washed and dried at 70° C., and the modified porous material with different pore sizes loaded with the pigment is obtained after grinding; Step 3: prepare a PVP / ethanol solution with a mass concentration of 10-14%, add the modified porous materials with different pore sizes loaded with pigments, stir evenly and place in an electrospinning device for electrospinning to obtain a porous fiber membrane coated with pigments; Step 4: remove the pigment-coated porous fiber membrane, put it into a vacuum drying oven at 70°C, crush it, and pass it through a 200-mesh sieve to obtain pigment-coated porous fiber membrane particles with a porosity of 60-80% and a pore size of 10-50 μm; Step 5: dissolving chitosan in 3% acetic acid solution to prepare a 0.5-2 g / L chitosan acetic acid solution; taking 50 mg of attapulgite nanorods, adding 50 mL of PBS buffer, and ultrasonically dispersing to obtain a attapulgite nanorod suspension; Step 6: immerse 50 mg of the pigment-encapsulated porous fiber membrane particles in 100 mL of chitosan acetic acid solution for 1 to 2 h; Step 7: Add the attapulgite nanorod suspension, stir and mix evenly, and perform electrostatic assembly reaction at room temperature for 4 to 5 hours; Step 8: Take out the reactants, wash with water, and freeze-dry to obtain highly stable pigment particles.

3. The non-fading masterbatch for lawn use according to claim 2, characterized in that: The preparation method of porous materials with different pore sizes in step 1 is as follows: S1: 3g MgO, 18g Al2O3 and 80g SiC powders were mixed evenly, 0.8wt.% sodium carboxymethyl cellulose solution was added, and the pH was adjusted to 10 to obtain a ceramic slurry with a solid content of 25-40vol.%; S2: placing the ceramic slurry in a ball mill for ball milling, the ball milling time is 10 hours, and the rotation speed is 100r / min; S3: adding the milled ceramic slurry to PS microspheres of different particle sizes, stirring evenly, injecting into the mold, and centrifuging at 4000-6000 rpm for 30-50 min on a centrifuge; S4: Immerse the bottom of the mold in a liquid cold source at -120°C to -30°C and freeze it quickly; S5: freeze-drying at a temperature of -50°C and a pressure of 0-50Pa to obtain porous ceramic preforms with different pore sizes; S6: Place the porous ceramic preforms with different pore sizes into an atmosphere box furnace, keep them in air at 385°C for 20 minutes, then heat them to 1200°C for 1 hour, introduce argon gas for liquid phase sintering after vacuuming, heat them to 1500°C for 2 hours, and heat them at a rate of 5°C / min.

4. The non-fading masterbatch for lawn use according to claim 2, characterized in that: The addition amount of the PS microspheres with different particle sizes is 1-2% of the volume of the ceramic slurry, the particle sizes are 10-30nm and 100-170nm respectively, and the volume ratio is 1:

1.

5. The non-fading masterbatch for lawn use according to claim 2, characterized in that: In the step 1, the volume mass ratio of the chitosan acetic acid solution and the porous materials with different pore sizes is 1L:(50-130)g.

6. The non-fading masterbatch for lawn use according to claim 2, characterized in that: The particle size of the modified porous material with different pore sizes loaded with pigment in step 2 is 2 to 20 μm.

7. The non-fading masterbatch for lawn use according to claim 2, characterized in that: In step 3, the volume mass ratio of the PVP / ethanol solution to the modified porous materials with different pore sizes is 20 mL: (1-2) g.

8. The non-fading masterbatch for lawn use according to claim 2, characterized in that: The electrospinning conditions in step 3 are as follows: spinning temperature is 20-26° C., humidity is 20-30%, spinning solution flow rate is 0.5-0.8 mL / h, needle outer diameter is 0.8 mm, inner diameter is 0.5 mm, and receiving distance is 13-16 cm.

9. The method for preparing a non-fading masterbatch for lawn use according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Mix low-density polyethylene, polyethylene wax and magnesium stearate with high-speed stirring, and heat to 80° C. and maintain the temperature until the polyethylene wax is completely melted; Step 2: Add high-stability pigment particles and stir until a large amount of high-stability pigment particles are coated on the surface of the low-density polyethylene to obtain a mixture; Step 3: After the twin-screw extruder is heated to 130°C, add the mixed material, extrude and granulate at a temperature of 120-140°C to obtain the non-fading masterbatch for lawn use.

Citation Information

Patent Citations

  • Polyethylene color master batch and preparation method thereof

    CN111423649A

  • Color masterbatch production process improving coloring uniformity of plastic color masterbatch

    CN111534003A

  • Preparation method of high-weather-resistance low-yellowing colored polycarbonate color master batch

    CN113185826A

  • Weather-resistant color master batch and preparation method thereof

    CN114249935A

  • Color master batch with uniform color and luster for artificial turf and preparation method of color master batch

    CN118290838A